1991
DOI: 10.1177/070674379103600912
|View full text |Cite
|
Sign up to set email alerts
|

Penile Self-Mutilation Presenting as Rational Attempted Suicide

Abstract: Genital self-mutilation is rare, and reports suggest that it is usually associated with psychotic illness. We report a case in which penile self-mutilation was an attempt to commit suicide and justified as a rational action. The literature on genital self-mutilation is reviewed. It is argued that the strong association between genital self-mutilation and psychosis may be the result of selective reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…This may be the result of selective reporting 4. This is an unusual case of genital self-mutilation in erectile disorder.…”
Section: Discussionmentioning
confidence: 92%
“…This may be the result of selective reporting 4. This is an unusual case of genital self-mutilation in erectile disorder.…”
Section: Discussionmentioning
confidence: 92%
“…19 Conacher et al reported a case in which penile self-mutilation was an attempt to commit suicide too. 20 A suicide case, realized by a 31-year-old man with multiple slashes and stab wounds including complete amputation of penis, scrotum and testicles was reported by Keil et al They stated that despite serious loss of blood, the reported survival periods were remarkable and death from bleeding seemed to be rare. 21 Therefore, the genital self-amputation act of our case may also be considered a failed suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Because GSM is considered bizarre behaviour, there is a tendency to assume that the victims are psychotic [16–18]. Greilsheimer and Groves categorized genital self‐mutilators into two broad groups, those who are psychotic (87%) or not [17].…”
Section: Psychiatric Assessmentsmentioning
confidence: 99%
“…While suicide attempts may be occasionally rational [5], the bizarre nature of several cases is obvious. It is believed by many people that amputation of the male phallus is fatal [16, 32] and it has been suggested that GSM among the Chinese be considered a suicide attempt [32].…”
Section: The Motivesmentioning
confidence: 99%